Assembly of Fe3O4 nanoparticles on PEG-functionalized graphene oxide for efficient magnetic imaging and drug delivery1. Issue 85 (16th September 2015) - Chen, Weihong; Wen, Xin; Zhen, Guorong; Zheng, Xiuwen
<x xml:space="preserve">Abstract</x> We have developed a strategy for preparation of Fe3O4–PEG–GO/DOX nanocomposites for efficient magnetic imaging and drug delivery.